2022
DOI: 10.3389/fimmu.2022.1014515
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology approaches to investigate the role of granulomas in TB-HIV coinfection

Abstract: The risk of active tuberculosis disease is 15-21 times higher in those coinfected with human immunodeficiency virus-1 (HIV) compared to tuberculosis alone, and tuberculosis is the leading cause of death in HIV+ individuals. Mechanisms driving synergy between Mycobacterium tuberculosis (Mtb) and HIV during coinfection include: disruption of cytokine balances, impairment of innate and adaptive immune cell functionality, and Mtb-induced increase in HIV viral loads. Tuberculosis granulomas are the interface of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
(194 reference statements)
0
2
0
Order By: Relevance
“…When HIV is co-infected, the likelihood of active tuberculosis disease is 15-21 times higher than when tuberculosis is the only infection and mycobacterium tuberculosis co-infection Health Dynamics is a major factor in mortality in HIV-infected people. (3,4) The epidemiology of these two illnesses may interact and be influenced by each other's causes. (5) According to Bell & Noursadeghi, (2017) HIV coinfection substantially increases the risk of developing active TB and conversely, TB co-infection will increase the rate of replication, spread, and genetic diversity of HIV-1.…”
Section: Introductionmentioning
confidence: 99%
“…When HIV is co-infected, the likelihood of active tuberculosis disease is 15-21 times higher than when tuberculosis is the only infection and mycobacterium tuberculosis co-infection Health Dynamics is a major factor in mortality in HIV-infected people. (3,4) The epidemiology of these two illnesses may interact and be influenced by each other's causes. (5) According to Bell & Noursadeghi, (2017) HIV coinfection substantially increases the risk of developing active TB and conversely, TB co-infection will increase the rate of replication, spread, and genetic diversity of HIV-1.…”
Section: Introductionmentioning
confidence: 99%
“…Though the primary function of granuloma is to contain the bacilli, in some instances, the bacilli can survive inside these structures for extended periods of time in a dormant state. Under immunosuppressive conditions, such as HIV co-infection, the bacilli escape the granuloma and spread to extrapulmonary organs causing the reactivation of LTBI [ 6 , 11 , 12 ]. Nonhuman primate (NHP) research has shown that there are direct cytopathic effects of Simian Immunodeficiency Virus (SIV) resulting in chronic immune activation, altered effector T cell phenotypes, and dysregulated T cell homeostasis that causes LTBI reactivation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%